Increased mortality risk for adults aged 25-44 years with long-term disability: A prospective cohort study with a 35-year follow-up of 30,080 individuals from 1984-2019 in the population-based HUNT study - Ellen Melbye Langballe; Gro Gujord Tangen; Bo Engdahl; Bjørn Heine Strand (Elsevier, 2022)
Summary: Background: Differences in survival between groups may reflect avoidable and modifiable inequalities. This study examines the 35-year mortality risk for adults aged 25-44 years in the mid-1980s with disability due to vision, hearing, or motor impairment; physical illness; or mental health problems. Methods: This Norwegian study was based on data from the Trøndelag Health Study (HUNT1, 1984-86, and HUNT2, 1995-97) linked to tax-registry data for deaths before 15 November 2019. Mortality risk was estimated by Cox regression analysis adjusted for age and sex. Sensitivity analysis included the following possible mediators: education, work, living situation, body mass index, systolic blood pressure and smoking. Findings: Of the 30,080 HUNT1 participants aged 25-44 years, 5071 (16.9%) reported having disability. During the 35 years of follow-up, 1069 (21.1%) participants with disability and 3107 (12.4%) without disability died. Individuals with any type of disability had 62% higher mortality risk compared to those without a disability, adjusted by age and sex. The highest mortality risks were observed for disability due to severe motor impairment (HR=3.67, 95%CI=2.89-4.67) and severe mental health problems (HR=3.40, 95%CI=2.75-4.23) compared to those without these disabilities. Increased mortality risk was found for all the included disability types. The associations were somewhat mediated, especially by education, work and living situation. Interpretation: This study shows that among adults aged 25-44 years, the risk of death increases with disability of different types and severity levels, particularly for disability related to mental health problems or motor impairment. Funding: None.